The Natural History and Treatment Strategy of Gastric Adenoma as a Pre-cancerous Lesion - Soo In Choi; Jun Chul Park (Yong Chan Lee, 2018)
The concept and pathological diagnostic criteria of gastric adenoma (dysplasia) differ between Western countries and Japan, and discrepancies between histopathological examinations before and after endoscopic resection may occur. Therefore, the natural history of adenoma should be interpreted and the treatment strategy of adenoma established. It is recommended that endoscopic resection be performed for high-grade dysplasia due to the potential higher risk of progression to carcinoma. For low-grade dysplasia, the risk of malignant transformation is relatively low. However, resection is considered the first approach for the purpose of diagnosis and treatment. If resection is not feasible, the alternative may be to use argon plasma coagulation for selected lesions that are less likely to be malignant. When Helicobacter pylori infection is detected, eradication therapy is recommended to reduce the risk of metachronous lesions. Post-resection follow-up should be performed within 1 year to detect synchronous lesions and then follow-up endoscopy at 1 or 2-year intervals may be considered for metachronous lesions.